24 Citizens' utilisation and satisfaction with a novel organisational structure of prehospital access to hospital care. (21st May 2017) - Gamst-Jensen, H; Blomberg, N; Folke, F; Lippert, F
Abstract : Aim: The ambulance service (EMS) and out-of-hours service (OOH) of Capital Region of Copenhagen (EMS Copenhagen) was united January 1st 2014, featuring only two phone numbers to call in case of acute illness or injury: 112 for life threatening conditions, and 1813 for non-urgent conditions. All prehospital access to in-hospital acute care is pre-assessed and guided to the nearest appropriate hospital with least waiting time (capacity controlling). The aim of this study was to describe citizens' utilisation and satisfaction with the Copenhagen-Model (CM). Methods: Data was delivered by the Emergency Departments (ED) database and the internal database for EMS Copenhagen. Utilization-analysis of OOH and ED components before (2013) and after (2014–2015) implementation of the new structure was examined. Satisfaction-analysis with the CM was evaluated by an external facility April 1st to October 1st (2171 questionnaires – response-rate 36%). Results: The OOH service (1.8 million inhabitants) receives approx. 265 calls/1000 citizens annually. The introduction of the CM resulted in a decrease of contacts to the ED – 5 66 606 contacts in 2013 to 5 16 738 and 4 97 389 contacts in 2014 and 2015, respectively (p<0.05). Capacity controlling showed that citizens referred to ED for emergency triage had an average time from call to treatment-start of 62 min (non-urgent 93 min). Approx. 93% of callers to the OOH had a good-very good experience with the service. Conclusion: EMS capacity controlling for non-urgent conditions showed a significant decrease in ED contacts, and has proven successful with 93% of callers having a good-very good experience with the service. Conflict of interest: None declared. Funding: EMS Copenhagen receives centre support from The Laerdal Foundation. The corresponding author has received grants from Trygfonden. Non of these organisations have had any influence on the study.